Dispositivo com monitoramento remoto que libera comprimidos aos idosos - Santos, Ana Carolina Ribeiro dos (2019)
New technologies have been implemented in the health area to guarantee a higher quality of life for elderlies. Therefore, an alternative was developed to help the correct intake of long-term medications by the elderly: a device that uses several tools from the platform of Raspberry Pi 3 and that has its code of programming elaborated in the Python language. The buzzer, the LEDs and the motors are activated from data obtained from several sensors. This gadget is also capable of receiving and sending information through a web page that uses a wireless connection, ensuring the caregivers to monitor and operate the equipment from a distance. In this paper are highlighted existing technologies that support the need of the project, analyzing the components, protocols and development tools that meet the demands and requirements of the system. The results were satisfactory by implementing the knowledge obtained from previous research and clinical trials, since the connection established between the Web page and the prototype worked correctly. It is also perceived that the tool developed can assist users and caregivers in the handling of medications, ensuring greater safety in the consumption of medications by the elderly.